Implementation of the Kulliyatul Mu'allimin Al-Islamiyah (KMI) Curriculum in the Development of Noble Morals Students at Khaira Ummah Islamic Boarding School Southeast Aceh - Hidayat, Farhan; Asari, Hasan; Dahlan, Zaini (Electronic Journal of Education, Social Economics and Technology, 2024)
National character building has been a priority for Indonesia since 1945 and is integrated into national development. National education plays an important role in shaping a generation that is faithful, pious, and has noble character. However, globalization and the information revolution present major challenges, including the influence of foreign cultures that can shift local values. Islamic boarding schools, as traditional Islamic educational institutions, are required to adapt in order to maintain their relevance in shaping national character in the modern era. Therefore, innovation and transformation are needed in the Islamic boarding school education system to prepare students to face the modern world while maintaining noble values. Khaira Ummah Islamic Boarding School, as a modern Islamic educational institution, adopts the learning system from the Modern Darussalam Gontor Islamic Boarding School, including the KMI (Kulliyatul Mu'allimin Al-Islamiyah) Curriculum. This approach combines traditional values with modern educational methods to create a conducive learning environment for the formation of character and intellectualism of students. This study aims to describe and analyze the planning, implementation, and evaluation of the KMI curriculum in fostering noble character of students at Khaira Ummah Islamic Boarding School . In this study, the researcher used a qualitative approach with a case study research type. Data collection was obtained through observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions, while checking the validity of the data was carried out by extending participation, observation accuracy, triangulation. The results of the study indicate that the implementation of the KMI curriculum in the process of fostering noble morals of students at the Khaira Ummah Islamic Boarding School has been running well and has achieved a number of significant advances. Although there is room for improvement, especially in terms of facilities and infrastructure, curriculum development, improving the quality of human resources, more effective supervision, and a more comprehensive evaluation process, the steps that have been taken show a strong commitment to improving the quality of fostering morals of students. Although there are still challenges faced, the efforts made to achieve the goal of fostering noble morals have shown encouraging results and have the potential to achieve more optimal results. The difficulties faced are seen as opportunities to continue learning and developing, as well as important steps in the process of continuous improvement that will bring the Khaira Ummah Islamic Boarding School to a higher level of success in fostering the noble morals of its students.